Medical Psychological Approach In The Development Of Early Diagnosis And Treatment Of Children`S Crossbite - Azimova Shakhnoza Shukhratovna (Genius Publishing Group, 2021)
Anomalies of occlusion of dentition belong to the group of major dental diseases and are characterized by high prevalence. Their frequency and prevalence in temporary bite has increased significantly in recent decades, ranging from 17 to 100% [1, 14, 21, 22, 25]. Despite the implementation of preventive programs and the introduction of advanced medical technologies, the prevalence of dental anomalies in children over the past ten years has not tended to decrease and remains high both in Uzbekistan and abroad. Anomalies of occlusion of dentition have a high prevalence in young children [19,20,22, 25]. In particular, F. Y. Khoroshilkina (1999) indicates that according to the results of studies, dental anomalies on average occurred during the period of milk bite – in 24%, during the shift period – in 49%, during the permanent period, at the age of 17 - in 35%. The number of anomalies in the period from the beginning of the formation of a temporary bite to the beginning of a replacement increased by 25%.
Keywords: Crossbite; early diagnosis; treatment; medical and psychological approach